The Utility of Intraventricular Pressure Gradient for Early Detection of Chemotherapy-Induced Subclinical Cardiac Dysfunction in Dogs - Katsuhiro Matsuura (Animals, 2021)
Early detection of doxorubicin (DXR)-induced cardiomyopathy (DXR-ICM) is crucial to improve cancer patient outcomes and survival. In recent years, the intraventricular pressure gradient (IVPG) has been a breakthrough as a sensitive index to assess cardiac function. This study aimed to evaluate the usefulness of IVPG for the early detection of chemotherapy-related cardiac dysfunction. For this purpose, six dogs underwent conventional, speckle tracking, and color M-mode echocardiography concomitantly with pressure-and-volume analysis by conductance catheter. The cardiac function measurements were assessed before DXR administration (baseline, Pre), at the end of treatment protocol (Post), and at 1.5 years follow-up (Post2). The result showed a significant reduction in the left ventricular end-systolic pressure-volume (Emax: 4.4 ± 0.7, 6.1 ± 1.6 vs. 8.4 ± 0.8 mmHg/mL), total-IVPG (0.59 ± 0.12, 0.62 ± 0.15 vs. 0.86 ± 0.12 mmHg), and mid-IVPG (0.28 ± 0.12, 0.31 ± 0.11 vs. 0.48 ± 0.08 mmHg), respectively in Post2 and Post compared with the baseline (p < 0.05). Mid-to-apical IVPG was also reduced in Post2 compared with the baseline (0.29 ± 0.13 vs. 0.51 ± 0.11). Meanwhile, the fraction shortening, ejection fraction, and longitudinal strain revealed no change between groups. Total and mid-IVPG were significantly correlated with Emax (R = 0.49; p < 0.05, both) but only mid-IVPG was a predictor for Emax (R2 = 0.238, p = 0.040). In conclusion, this study revealed that impairment of contractility was the initial changes observed with DXR-ICM in dogs and only IVPG could noninvasively detect subclinical alterations in cardiac function. Color M-mode echocardiography-derived IVPG could be a potential marker for the early detection of doxorubicin cardiomyopathy.